1994
DOI: 10.1128/aem.60.11.4001-4008.1994
|View full text |Cite
|
Sign up to set email alerts
|

A novel strictly anaerobic recovery and enrichment system incorporating lithium for detection of heat-injured Listeria monocytogenes in pasteurized milk containing background microflora

Abstract: Heat-injured cells of Listeria monocytogenes were recovered from heated raw milk containing noninjured Enterococcusfaecium by combining a simple method for obtaining strict anaerobiosis with a novel enrichment broth, Penn State University broth (PSU broth). Strictly anaerobic conditions were rapidly achieved by adding 0.5 g of filter-sterilized cysteine per liter to PSU broth and then purging the preparation with N2 gas. Little resuscitation or growth occurred in strictly anaerobic PSU broth without lithium ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
(56 reference statements)
3
13
0
Order By: Relevance
“…Among the four kosmotropic solutes tested, the alkali metal lithium was found to be the most thermoprotective at both 50°C and 70°C. This finding is consistent with previous studies where Listeria monocytogenes heated in raw milk at 62.8°C for 10, 15, and 20 min was recovered after 48, 96 and 144 h 775 respectively, by adding 7 g L -1 LiCl to the revival culture incubated at 30°C in rich heterotrophic medium (Mendonca and Knabel, 1994). Thermoprotective effect of lithium could be linked, but not necessarily restricted, to its activities at the periphery of cells.…”
Section: Kosmotropic Solutes Increase the Proportion Of Ready-to-divisupporting
confidence: 92%
“…Among the four kosmotropic solutes tested, the alkali metal lithium was found to be the most thermoprotective at both 50°C and 70°C. This finding is consistent with previous studies where Listeria monocytogenes heated in raw milk at 62.8°C for 10, 15, and 20 min was recovered after 48, 96 and 144 h 775 respectively, by adding 7 g L -1 LiCl to the revival culture incubated at 30°C in rich heterotrophic medium (Mendonca and Knabel, 1994). Thermoprotective effect of lithium could be linked, but not necessarily restricted, to its activities at the periphery of cells.…”
Section: Kosmotropic Solutes Increase the Proportion Of Ready-to-divisupporting
confidence: 92%
“…The presence of LiCl, even in low concentrations, inhibits bacterial growth by competing with essential divalent cations, such as calcium and magnesium. It is possible that critical metalloenzymes are inactivated when the monovalent cation Li + replaces divalent cations on these enzymes (Mendonca and Knabel, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The pelleted THP‐1 cells were re‐suspended in 2 mL of PBS, washed with this volume of medium two times by centrifugation at 800 g for 7 min, re‐suspended in 1 mL of water to lyse the THP‐1 cells, and after concentration via high‐speed centrifugation, the entire lysate was plated. Mendonca [12] reported that noncultivable Listeria could be recovered only under strictly anaerobic conditions. Accordingly, we plated the lysate on FAA plates and incubated them under anaerobic conditions at 37 °C for 14 days.…”
Section: Methodsmentioning
confidence: 99%